Efficacy of Various Routes of Dexamethasone Administration in Reducing Postoperative Sequelae Following Impacted Third Molar Surgery - Vivek, G.K. (Ann Maxillofac Surg, 2020)
AIM: To compare the efficacy of intravenous (IV), intramassetric (IM) submucosal (SM) routes & oral routes of dexamethasone administration post impacted third molar removal surgery. TYPE OF STUDY: Prospective randomized comparative clinical study. MATERIALS AND METHOD: This prospective comparative study included 60 patients with Class II and position B type of impaction (according to Pell and Gregory's classification). Patients were randomly divided into 4 groups. Group A, B, C & D patients received 8mg dexamethasone immediately post-surgical tooth removal via the IV, SM and IM route & oral respectively. Assessment of swelling, mouth opening and pain was done at intervals of 1st, 3rd and 7th post-op days. RESULTS: The average age of the patients was 27 years. The mean time taken was 20 mins 40 seconds. The IV group showed minimal swelling and better pain control on the 3rd post op day (statistically significant). All 4 routes showed comparable mouth opening results. CONCLUSION: IV administration of dexamethasone post third molar surgery has been the traditional way because of its faster onset of action and increased efficacy; IM and SM routes are also comparably effective although oral route had the best patient acceptance.